Mannan‐binding lectin‐associated serine protease 2 is critical for the development of renal ischemia reperfusion injury and mediates tissue injury in the absence of complement C4. Issue 9 (27th May 2014) - Asgari, Elham; Farrar, Conrad A.; Lynch, Nicholas; Ali, Youssif M.; Roscher, Silke; Stover, Cordula; Zhou, Wuding; Schwaeble, Wilhelm J.; Sacks, Steven H.
Abstract : Mannan‐binding lectin‐associated serine protease 2 (MASP‐2) has been described as the essential enzyme for the lectin pathway (LP) of complement activation. Since there is strong published evidence indicating that complement activation via the LP critically contributes to ischemia reperfusion (IR) injury, we assessed the effect of MASP‐2 deficiency in an isogenic mouse model of renal transplantation. The experimental transplantation model used included nephrectomy of the remaining native kidney at d 5 post‐transplantation. While wild‐type (WT) kidneys grafted into WT recipients ( n =7) developed acute renal failure (control group), WT grafts transplanted into MASP‐2‐deficient recipients ( n =7) showed significantly better kidney function, less C3 deposition, and less IR injury. In the absence of donor or recipient complement C4 ( n =7), the WT to WT phenotype was preserved, indicating that the MASP‐2‐mediated damage was independent of C4 activation. This C4‐bypass MASP‐2 activity was confirmed in mice deficient for both MASP‐2 and C4 ( n =7), where the protection from postoperative acute renal failure was no greater than in mice with MASP‐2 deficiency alone. Our study highlights the role of LP activation in renal IR injury and indicates that injury occurs through MASP‐2‐dependent activation events independent of C4.—Asgari, E., Farrar, C. A., Lynch, N., Ali, Y. M., Roscher, S., Stover, C., Zhou, W., Schwaeble, W. J., Sacks, S. H. Mannan‐binding lectin‐associated serine protease 2 is critical for the development of renal ischemia reperfusion injury and mediates tissue injury in the absence of complement C4. FASEB J. 28, 3996‐4003 (2014). www.fasebj.org